Neutral and cationic osmium(II)-arene metallodendrimers: Synthesis, characterisation and anticancer activity - Govender, Preshendren; Edafe, Fabio; Makhubela, Banothile C. E.; Dyson, Paul J.; Therrien, Bruno; Smith, Gregory S. (My University, 2014)
Two neutral and two cationic half-sandwich Os(II)-arene metallodendrimers, [DAB-PPI-{(?6-p-cym)Os((C7H5NO)-?2-N,O)Cl}n] and [DAB-PPI-{(?6-p-cym)Os((C6H5N2)-?2-N,N)Cl}n][PF6]n (n = 4 (G1) or 8 (G2)) were synthesized. Two cationic half-sandwich Os(II)-arene metallodendrimers, contg. PTA (1,3,5-triaza-7-phosphatricyclo[3.3.1.1.] decane), [DAB-PPI-{(?6-p-cym)Os((C7H5NO)-?2-N,O)PTA}n][PF6]n are also reported. All complexes were characterized using anal. (i.e. HR-ESI or EI mass spectrometry and elemental anal.) and spectroscopic (i.e.1H, 13C{1H} NMR and IR) methods. Model mononuclear analogs were prepd. and their mol. structures detd. by single-crystal x-ray crystallog. The cytotoxicity of the complexes were evaluated against the A2780 and A2780cisR human ovarian carcinoma cell lines and some display moderate activity. [on SciFinder(R)]
Keywords: cymeneosmium complex cyclometalation Schiff base salicylaldimine dendritic scaffold; cymene osmium salicylaldimine metallodendrimer prepn cytotoxicity anticancer agent; crystal structure neutral cationic cymene osmium salicylaldimine metallodendrimer; mol structure neutral cationic cymene osmium salixylaldimine metallodendrimer